From nano- to macro-scale: nanotechnology approaches for spatially controlled delivery of bioactive factors for bone and cartilage engineering - Santo, Vítor E; Gomes, Manuela E; Mano, João F; Reis, Rui L (Nanomedicine (London, England), 2012)
The field of biomaterials has advanced towards the molecular and nanoscale design of bioactive systems for tissue engineering, regenerative medicine and drug delivery. Spatial cues are displayed in the 3D extracellular matrix and can include signaling gradients, such as those observed during chemotaxis. Architectures range from the nanometer to the centimeter length scales as exemplified by extracellular matrix fibers, cells and macroscopic shapes. The main focus of this review is the application of a biomimetic approach by the combination of architectural cues, obtained through the application of micro- and nanofabrication techniques, with the ability to sequester and release growth factors and other bioactive agents in a spatiotemporal controlled manner for bone and cartilage engineering.